DOES THE RISK DISCLOSURE DECREASE COST OF DEBT? : Empirical study on Consumption Sector Companies Listed on the Indonesia Stock Exchange for the period of 2019 to 2022 - Karsana, Yusef Widya (FEB Universitas Sam Ratulangi Manado, 2024)
This research aims to find out whether Risk Disclosure can reduce debt costs for public companies in Indonesia, especially for consumption sector companies. The period in this research is 2019 to 2022. Risk Disclosure is measured using content analysis. The hypothesis was tested using panel data regression analysis with a Random Model and adding control variables consisting of Return On Equity, Leverage, Firm Size, and proportion of independent commissioners. The results of this research indicate that risk disclosure has a positive effect on the cost of debt. This means that the higher risk disclosure does not reduce the cost of debt, but even increases the cost of debt. This finding is contrary to the hypothesis which states that risk disclosure has a negative influence on the cost of debt. The control variables that influence the cost of debt are Company size and the proportion of independent commissioners, while Return On Equity and Leverage do not influence the cost of debt. These findings provide a reference about the consequences of risk disclosure on the Company's cost of debt. Research on the cost of debt is very relevant in Indonesia because many companies still rely on creditors for funding. Keywords: Cost of Debt, Risk Disclosure (RD), consumption sector.